School based factors affecting learning of Kenyan sign language in primary schools for hearing impaired in Embu and Isiolo counties, Kenya - Samuel Muthomi Rwaimba (Universidade Federal do Norte do Tocantins, 2016)
This was a descriptive survey study design which sought to establish the school based factors that affect the learning of Kenyan Sign Language in primary schools for learners with hearing impairment in Embu and Isiolo counties in Kenya. The target population was all teachers teaching in primary schools for learners with hearing impairment in the two counties. From the selected schools, the study purposively and randomly sampled 2 head teachers and 8 teachers respectively. Interview guides were used to obtain data from the head teachers, questionnaires from teachers while observation schedules were used to obtain data on the general nature of the school environment. Quantitative data collected were analyzed using descriptive statistics and tabulated in frequency tables, bar charts and pie charts while qualitative data were analyzed and presented in narrative form. The study findings revealed that all the sampled respondents had training in special needs education but only 25% had training in KSL as a subject. Basing on the findings the researcher recommends that the TSC should post only teachers trained in KSL to teach KSL among learners with HI and that the universities should introduce KSL as a teaching subject alongside other subjects like Mathematics, English and Kiswahili.